Co-rotational formulation of a solid-shell element utilizing the ANS and EAS methods - Polat, Cengiz (Polish Society of Theoretical and Allied Mechanics, 2010)
An efficient eight-node solid-shell element is demonstrated. The Assumed Natural Strain (ANS) and the Enhanced Assumed Strain (EAS) methods are used to alleviate the locking problems. A co-rotational formulation is adopted in the description, thus geometric nonlinearity is taken into account by rotation of the local coordinate system. Several benchmark problems are examined to demonstrate the efficiency of the element.
Keywords: ANS-EAS method; Co-rotational formulation; Solid-shell element